Impact of ship emissions on local air quality in a Mediterranean city's harbour after the European sulphur directive. (2016) - Buccolieri, Riccardo; Cesari, Rita; Dinoi, Adelaide; Maurizi, Alberto; Tampieri, Francesco; Sabatino, Silvana Di
We present a modelling approach to investigate the impact of ship emissions in the port of Brindisi (IT) on local air quality. The focus is on the impact on pollutant concentrations due to the implementation of the MARPOL Annex VI and the associated NOx technical code 2008 (concerning NOx emissions) and the Directives 2005/33/EU-2012/33/EU (concerning the sulphur content of maritime fuels). Emissions are estimated through an adapted MEET methodology using appropriate emission factors for manoeuvring and hotelling phases. Numerical simulations of NOx, SO2 and primary PM10 are performed by means of the mesoscale model BOLCHEM coupled off-line with ADMS-Urban. The impact of present and future ship emissions on air quality in the port area is evaluated. After the implementation of the Directives 2005/33/EU-2012/33/EU for the year 2012 SO2 showed a significant concentration reduction especially close to the port area, while primary PM10 concentration reduction was minor, as well as that of NOx, as a consequence of the NOx technical code. No significant reductions were found for the year 2020.